ECONOMIC COMMUNITY EMPOWERMENT STRATEGIES IN BANJARMASIN BASED ON ENVIRONMENT CHARACTERISTIC FINANCIAL MODEL - Syabarrudin, Agus; Ahmad Alim Bachri; Udiannoor; Hamdani (Dinasti International Journal of Digital Business Management, 2020)
The objectives of the research conducted in Banjarmasin City are: 1) To assess and analyze economic financing patterns in the community based on slum environmental characteristics, 2) To assess and analyze the level of economic empowerment in the community, 3) To assess and analyze the characteristics of communities targeted for slum environment empowerment , 4) Identify and analyze community economic empowerment strategies through financing models for slums environment. The research method used in this study is quantitative descriptive supported by qualitative descriptive. The result of this prospective study suggests that further research needs to be done to focus on the appropriate financing model for the empowerment of slum community in Banjarmasin.